BUILDING A FRAMEWORK OF CRITERIA FOR ASSESSING ACCOUNTABILITY IMPLEMENTATION RESULTS OF PUBLIC UNIVERSITIES - Pham Le Cuong, Pham Minh Hung* (Tạp chí Khoa học)
University autonomy is the most important feature of modern education and is associated with accountability. By implementing the autonomy mechanism associated with accountability, universities will maximize their resources to continuously improve the quality of training, scientific research and community service. Based on the identified bases, the article proposes a Criteria Framework to evaluate the results of implementing accountability in public universities, including 03 standards and 18 criteria. This criteria framework can be used to evaluate the accountability performance of each public university.